Relationship Knowledge And Anxiety Levels On Sexual Relationships In Pregnancy - Arum Meiranny; Alfiah Rahmawati; Verawati Verawati (Alma Ata University Press, 2020)
Sex is a biological need that must be met in the life of a married couple. With sexual intercourse, the household becomes harmonious and peaceful. Sexual intercourse is a routine activity almost every day. This is of course different when the wife is pregnant, the sexual relations between husband and wife will certainly decrease. To determine whether there is a relationship between knowledge and anxiety levels on sexual intercourse in pregnancy. International literature is traced through electronic media with keyword guidance. 5 articles were selected, each of which represents a Knowledge Relationship and Anxiety Levels on Sexual Relations in Pregnancy and provides various information. Nearly half of the respondents experienced moderate anxiety during sexual intercourse during pregnancy. 53.7% of mothers have high knowledge on Trimester I Primigravida Pregnancy. 78% experience anxiety in Trimester I Primigravida Pregnancy. The conclusion based on the analysis that has been done is that there is a relationship between knowledge and anxiety levels about sexual relations in pregnancy.